Characterizing large deformation of soft rock tunnel using microseismic monitoring and numerical simulation - Yuepeng Sun; Nuwen Xu; Peiwei Xiao; Zhiqiang Sun; Huailiang Li; Jun Liu; Biao Li (Journal of Rock Mechanics and Geotechnical Engineering)
Surrounding rock deterioration and large deformation have always been a significant difficulty in designing and constructing tunnels in soft rock. The key lies in real-time perception and quantitative assessment of the damaged area around the tunnel. An in situ microseismic (MS) monitoring system is established in the plateau soft tock tunnel. This technique facilitates spatiotemporal monitoring of the rock mass's fracturing expansion and squeezing deformation, which agree well with field convergence deformation results. The formation mechanisms of progressive failure evolution of soft rock tunnels were discussed and analyzed with MS data and numerical results. The results demonstrate that: (1) Localized stress concentration and layered rock result in significant asymmetry in micro-fractures propagation in the tunnel radial section. As excavation continues, the fracture extension area extends into the deep surrounding rockmass on the east side affected by the weak bedding; (2) Tunnel excavation and long-term deformation can induce tensile shear action on the rock mass, vertical tension fractures (account for 45%) exist in deep rockmass, which play a crucial role in controlling the macroscopic failure of surrounding rock; and (3) Based on the radiated MS energy, a three-dimensional model was created to visualize the damage zone of the tunnel surrounding rock. The model depicted varying degrees of damage, and three high damage zones were identified. Generally, the depth of high damage zone ranged from 4 m to 12 m. This study may be a valuable reference for the warning and controlling of large deformations in similar projects.